1998
DOI: 10.1111/j.1558-5646.1998.tb05163.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Regeneration for a Neutralized Selfish B Chromosome

Abstract: Long-run evolution of B chromosomes is mainly made up by an evolutionary arms race between these selfish genetic elements and the standard genome. The suppression of B drive is one of the clearest expressions of genome defense against B chromosomes. After drive neutralization, the B is condemned to extinction unless a new variant showing drive can emerge and replace it. This paper reports the first empirical evidence for the substitution of a neutralized B variant by a new selfish B variant. Such a polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 15 publications
7
64
4
Order By: Relevance
“…This conclusion is valid for males, which were the subject of the current experiments, and it is consistent with the fact that B chromosomes in E. plorans are near-neutral with no significant effects on male fitness (Camacho et al 1997). Future studies should analyze the situation in females since a significant decrease in female fertility was reported in the population analyzed here (Zurita et al 1998) and thus the meaning of the rRNA contributed by the B chromosomes could be different.…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion is valid for males, which were the subject of the current experiments, and it is consistent with the fact that B chromosomes in E. plorans are near-neutral with no significant effects on male fitness (Camacho et al 1997). Future studies should analyze the situation in females since a significant decrease in female fertility was reported in the population analyzed here (Zurita et al 1998) and thus the meaning of the rRNA contributed by the B chromosomes could be different.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, in E. plorans, B chromosomes and mite ectoparasites decrease egg fertility (Muñoz et al 1998). In fact, the B chromosome variant showing the highest drive (B 24 in the Torrox population in 1992) in this species was also the one producing the largest decrease in egg fertility (Zurita et al 1998). In a previous work, we found that the Torrox population showed lower total NA per cell than two other populations (Salobreña in Spain and Smir in Morocco) carrying less parasitic B chromosomes, thus suggesting that parasitic Bs are associated with smaller nucleoli .…”
Section: Discussionmentioning
confidence: 97%
“…The most parasitic B was found in the Torrox (Málaga, Spain) population, where the B 24 variant was transmitted to 70% of progeny through females, and it significantly decreased egg fertility (Zurita et al 1998). Another sign of the parasitic nature of B 24 was a higher increase in cell chiasma frequency than other variants showing signs of neutralization (Camacho et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…These populations harbor the B2 and B24 variants, respectively, the latter being more parasitic and derived from the former (Zurita et al 1998). These authors found a decrease in the level of HSP70 protein in male and female gonads of B-carrying individuals from both populations, but HSP70 levels were lower in Torrox than Salobreña.…”
mentioning
confidence: 97%
“…The presence of B chromosomes can cause genetic stress on the individuals carrying them, or may affect carriers' ability to deal with stress, especially with high B numbers (Teoh and Jones 1978;Teruel et al 2011). Signs of stress associated with B-chromosome presence have been reported in the grasshopper Eyprepocnemis plorans, manifested through a decrease in eggs fertility and clutch size (Zurita et al 1998;Muñoz et al 1998;Bakkali et al 2010) and nucleolus size (Teruel et al 2007(Teruel et al , 2009), increase of chiasma frequency (Camacho et al 2002), and a general enhancement in transposable element transcription (Navarro-Domínguez et al in preparation) which could be associated with higher rates of transposition, a typical genomic reaction to stress (Arnault and Dufournel 1994). Likewise, transcriptome and microarray analyses have revealed that B-chromosome presence is associated with gene-expression changes related with protein modification and response to stress (Navarro-Domínguez et al in preparation).…”
mentioning
confidence: 98%